LIFE QUALITY OF PERSONS WITH ARTERIAL HYPERTENSION IN RUSSIA — IS THERE RELATION TO TREATMENT? (BY DATA FROM POPULATIONAL STUDY ESSE-RF) - Yu A. Balanova; A. V. Kontsevaya; S. A. Shalnova; A. D. Deev; A. V. Kapustina; S. E. Evstifeeva; G. А. Muromtseva; A. E. Imaeva; S. A. Boytsov (Российский кардиологический журнал)
Aim. To evaluate  LQ in AH patients,  to analyze the relation of LQ and  treatment status,  and to study associated with LQ factors, by the data of esse-Rf study. Material and methods. The materials for analysis were representative selections of inhabitants (n=21894) of 13 regions of Rf, included to esse-Rf study in 2012-2013  y. Response was  80%.  We used  standard epidemiological  methods   and criteria. The participants  were selected to 4 groups:  1) non-AH, 2) AH not taking AHD and having normal BP, 3) AH taking drugs  with non-controlled  hypertension (non-effective treatment), 4) AH not taking AHD. LQ was assessed with international eUROQOL-5D and visual analogue scale eQ-VAs. Integral LQ assessment was done with LW shaw et al. methodics. Into analysis the following were included: sex, age, education  and wealth levels, systolic and diastolic pressure, AH treatment status, comorbidities, region of participation.Results. In general,  women  with AH have  worse  LQ than  men  (p<0,0005).  In analysis of eQ-5D components we found, that prevalence  of prominent disorders was not higher than 3% for every single, but moderate disorders  reached 5-41% in those  with AH for different  parameters. eQ-VAs  were  significantly lower among those  having AH comparing  to non-AH — 66,4%  vs. 70,1%,  p<0,0005.  Highest values (p<0,0005) were found in those with AH not taking AHD, but AHD values in the group of those effectively managed and non-effectively managed were comparable. Total index of life quality by eQ-5D among men is higher than women (p<0,005), but it decreases with age.  Among both genders — in AH and  “AH not taking drugs” groups  — LQ by eQ-5D was comparable and  significantly higher than in groups “treated effectively” and “treated non-effectively”.Conclusion. Prevalence of AH in Rf remains high. LQ in AH persons is lower than in non-AH (mostly for those  taking AHD). This witnesses  on the necessity  for more attention  to  AH in real  clinical practice,   including  dispensary   observation  and involvement to educational  programs. The populational data obtained  in the study, of LQ in AH persons can be applied for QALY calculation in modelling of economical efficacy of various diagnostic  and management procedures in relation to Russian patients with AH.